Effect of microwave hybrid heating on mechanical properties and microstructure of Sn3.0Ag0.5Cu/Cu solder joints - Siti Rabiatull Aisha, Idris; M. N., Mazelan (Universiti Malaysia Pahang, 2023)
Microwave hybrid heating (MHH) has become soldering’s alternative method for lead-free solder alloys due to its benefits towards modern microtechnology, such as shorter processing time, lower energy consumption and lower defect rate. Nonetheless, it still requires susceptors to improve its heating performance, such as SiC, which is known for its high loss factor under low microwave frequencies. In this study, the effect of microwave hybrid heating on mechanical properties, as well as the microstructure of solder joint between Sn3.0Ag0.5Cu (SAC305) solder alloy and Cu substrate was investigated. Solder joint was created using MHH with different soldering parameters (amount of SiC in a range of 3-7g and exposure time in a range of 7-10min) between SAC305 solder alloy (in the form of wire and paste) and Cu substrate. Then, a lap shear test was carried out following a standard of ASTM D1002 to determine solder joint strength. Characterization was made using an optical microscope and scanning electron microscopy. Results showed that solder wire produced the highest solder joint strength with the value of 115.45 MPa when using 3.05g of SiC for 8.92min soldering time. Meanwhile, the solder paste produced 109.76MPa solder joint strength when using 3.03 g of SiC for 9.39 min soldering time. The intermetallic compound (IMC) form was scallop-like Cu6Sn5, both solder/substrate joints with a thickness of 2.87 μm for solder wire and 3.62 μm for solder paste. Nonetheless, an excessive amount of SiC would generate more heat in MHH and increase the IMC thickness as well as reduce shear strength, which eventually decreases the solder joint stability.